Implications of Operating Cash Flow and Market Valuation on Food and Beverage Industry Stock Returns - Metha Dwi Apriyanti; Yatimin Yatimin; Sisca Debyola Widuhung; Andry Priharta; Hendra Galuh Febrianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Background: The volatility of the capital market during the 2019–2023 period, encompassing the global pandemic and subsequent economic recovery, has underscored the need for a precise assessment of fundamental drivers in the defensive food and beverage sector. Objective: This study aims to empirically examine the influence of Operating Cash Flow (OCF), Capital Structure, Price Earnings Ratio (PER), and Net Profit Margin (NPM) on stock returns. Methodology: Employing a quantitative approach, the research utilizes panel data regression analysis on a purposive sample of food and beverage companies listed on the Indonesia Stock Exchange. Results: The findings demonstrate that while Operating Cash Flow fails to exert a significant partial effect, Capital Structure, PER, and NPM significantly determine stock returns. Furthermore, the simultaneous analysis confirms that these variables collectively possess substantial predictive power regarding market performance. Discussion/Novelty: This research makes a novel contribution by demonstrating that, during periods of economic transition, market valuation and profitability metrics remain more salient to investors than liquidity-based indicators. Conclusion/Contribution: These results offer critical strategic insights for investors in optimizing portfolio selection and for corporate management in formulating financial policies to maximize shareholder wealth.